AUTOMATIC EXTRACTION OF SEMANTIC ASSOCIATION FROM POLISH TEXT - Lubaszewski, Wieslaw; Gajecki, Marek (Computer Science, 2020)
In the paper we presents a methodfor automatic construction of an association listfor a particular word. Association list is a set o f word, each o f which is in a semantic relation with the words.to dejine. To construct the association list we use statistic reasoning algory- thm, which works on the base o f the Polish inflection dictionary, text corpus, and the quan- titative dictionary createdfor the corpus. Experiments are encouraging enough - one may think that the association can serve as the basefor the entry in a semantic dictionary.